Learning Strategies in the Implementation of the Islamic Education Curriculum at Nurul Ikhwan Kindergarten in Teluk Pulai Dalam, North Labuhanbatu - Aziz, Mursal; Asshiddiqi, Muhammad Hasbie; Ulfa, Maria (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2025)
Early childhood education (PAUD) plays a crucial role in character formation and child development, particularly within the context of Islamic-based education. Nurul Ikhwan Al-Qur'an Kindergarten (TKQ) in Teluk Pulai Dalam, North Labuhanbatu, is one of the educational institutions implementing the Islamic education curriculum at the TKQ level. However, implementing effective learning strategies amid limited facilities and time is challenging. This study aims to analyze the learning strategies used in implementing the Islamic education curriculum at Nurul Ikhwan TKQ. This study used a qualitative method with a descriptive analytical approach. Data were collected through observation, interviews with the principal and teachers, and analysis of documents related to the implemented curriculum. The results show that the implementation of the Islamic education curriculum at Nurul Ikhwan TKQ focuses on teaching the Quran and developing children's social character through lectures, question-and-answer sessions, and games. However, there are obstacles related to limited facilities and time, which affect the variety of learning methods. Teachers play a crucial role in the learning process, but they require more intensive training to address these challenges. Nevertheless, the positive impact on children's social character development is evident, particularly in their religious development and social interactions.